"For the Many": The Vicarious-Representative Heart of Joseph Ratzinger's Theology. (September 2014) - Ruddy, Christopher
The concept of vicarious representation ( Stellvertretung ) is central to Joseph Ratzinger's thought. He uses it, with its correlative concept of pro-existence, to develop a theology in which "the few" are the starting point from which God saves "the many." This article examines the concept's influence on Ratzinger's soteriology, Christology, and ecclesiology. It concludes by exploring four areas in which his vicarious-representative theology makes a significant contribution: the soteriological role of human freedom, the pro multis controversy, the "smaller but purer" criticism of his ecclesiology, and the Church's mission in a religiously plural world.